The State of Food and Agriculture 2012 (Food and Agriculture Organization of The United Nations (FAO), 2012)
The State of Food and Agriculture, FAO's major annual flagship publication, aims at bringing to wider audience balanced science-based assessments of important issues in the field of food and agriculture. Each edition of the report contains a comprehensive, yet easily accessible, overview of selected topic of major relevance for rural and agriculture development and for global food security.